2010
DOI: 10.1590/s0102-09352010000500026
|View full text |Cite
|
Sign up to set email alerts
|

Níveis de metionina + cistina digestíveis em rações para poedeiras no pico de produção

Abstract: RESUMOAvaliaram-se os efeitos de níveis de aminoácidos sulfurados digestíveis (AASD) sobre o desempenho e a qualidade interna e externa de ovos de 360 poedeiras de 25 a 41 semanas de idade. Foram formuladas seis dietas experimentais: cinco continham 0,578; 0,636; 0,694; 0,752 ou 0,810% de AASD, e em uma o nível de AASD foi o usualmente recomendado, cada tratamento com cinco repetições de 12 aves, em quatro períodos de avaliação de 28 dias cada. Melhores resultados para produção de ovos, conversão alimentar, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…These results are similar to the findings of Geraldo et al (2010), Jardim Filho et al (2004) and Prochaska and Corey (1993), who reported no lysine level effects on egg solids yields. However, in contrast to the present result, Geraldo (2006) found effects of digestible threonine levels on albumen solids.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These results are similar to the findings of Geraldo et al (2010), Jardim Filho et al (2004) and Prochaska and Corey (1993), who reported no lysine level effects on egg solids yields. However, in contrast to the present result, Geraldo (2006) found effects of digestible threonine levels on albumen solids.…”
Section: Resultssupporting
confidence: 91%
“…This behavior was also observed by Geraldo et al (2010), on evaluating hens subjected to different threonine levels in diets according to the Nutritional...…”
Section: Resultsmentioning
confidence: 54%